2022
DOI: 10.21203/rs.3.rs-2085777/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geodesic Tracking via New Data-driven Connections of Cartan Type for Vascular Tree Tracking

Abstract: We introduce a data-driven version of the plus Cartan connection on the homogeneous space $\mathbb{M}_2$ of 2D positions and orientations. We formulate a theorem that describes all shortest and straight curves (parallel velocity and parallel momentum, respectively) with respect to this new data-driven connection and corresponding Riemannian manifold. Then we use these shortest curves for geodesic tracking of complex vasculature in multi-orientation image representations defined on $\mathbb{M}_{2}$. The data-dr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…2a. In previous works by various authors, it has been shown that PDE-based geometric tracking algorithms [4,9,10,12] perform well in M 2 . Here, one first calculates a distance map which is based on the image data.…”
Section: Geodesic Tracking Of Retinal Vascular Trees With Optical And...mentioning
confidence: 95%
See 4 more Smart Citations
“…2a. In previous works by various authors, it has been shown that PDE-based geometric tracking algorithms [4,9,10,12] perform well in M 2 . Here, one first calculates a distance map which is based on the image data.…”
Section: Geodesic Tracking Of Retinal Vascular Trees With Optical And...mentioning
confidence: 95%
“…Applying the TV-flow enhancement in M 2 leads to crossing-preserving contextual denoising that preserves crossings, and line structures, and removes noisy non-aligned structures from the optical enhancement. Altogether the scheme results in a vascular tracking algorithm that provides better results as wavefronts follow the complex branching vasculature better than the approach in [4], see Fig. 1.…”
Section: Geodesic Tracking Of Retinal Vascular Trees With Optical And...mentioning
confidence: 99%
See 3 more Smart Citations